After the gas conflict: Economic consequences for Russia, Ukraine, and Germany - Roland Götz (Stiftung Wissenschaft und Politik (SWP), 2006)
In January 2006, the conflict between Russia and Ukraine over future gas prices, which had escalated by the end of 2005, was settled for the time being with a compromise. While the Russian company Gazprom has benefitted from the agreement, the reputation of Russia as a reliable energy supplier has been damaged. The case raises some additional questions: What strategy will Gazprom pursue in the post-Soviet area? Is Russia in a position to exert pressure on its European customers? What can the European Union, and in particular Germany, do to improve energy relations with Russia? (SWP Comments / SWP)
Keywords: 320